Bone mineral density in mountain, road cyclists and untrained controls: Exercise, diet and hormones - Zamboni, F.; Ferrari, P.; Cazzoletti, L.; Setti, A.; Bertoldo, F.; Dalle Carbonare, L. G.; Danese, E.; Tardivo, S.; Crisafulli, E.; Ferrari, M. (Research Quarterly for Exercise and Sport, 2024)
Purpose The aim of the study was to compare bone mineral density (BMD) in the lumbar spine (LSBMD) and the femoral neck (FBMD) in male road cyclists (RC n = 39), mountain cyclists (MC n = 30) and controls (C n = 27) and to determine the factors associated with BMD in the same group of participants.